2022
DOI: 10.1021/acsami.1c23708
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral-Framework Nucleic Acids Carry Small Interfering RNA to Downregulate Toll-Like Receptor 2 Gene Expression for the Treatment of Sepsis

Abstract: Sepsis is caused by the invasion of pathogenic microorganisms, which can lead to excessive expression of toll-like receptors (TLRs) in cells and uncontrollable amplification of the inflammatory response. TLR2, as an essential part of the TLR family, has a significant feature in the identification of innate immune responses. Therefore, blocking the expression and activation of TLR2 can inhibit the synthesis and release of inflammatory factors and avoid the occurrence of excessive inflammatory reactions. Small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…First, results of flow cytometry and immunofluorescence images showed that the nano‐windmill was taken up by bone marrow‐derived macrophages (BMDMs) in large quantities in a short time (Figure 2A,B), which revealed its effectively delivered capacities. Second, the RNase H‐responsive sequence was designed to be degraded after entering the cell (Figure 2C), while siR‐slc44a1 gradually dissociated from the nano‐windmill accompanied by the increase of RNase H concentration, identifying the successful separation of the nano‐windmill into tFNA and siR‐slc44a1 (Figure 2D), which is different from the previous tFNA‐based delivery system that tFNA released siRNA with breaking itself and loosing its intact structure after entry into cells, 33,34 such as the nanobox‐siR system 35 or modification of the S2 chain in tFNA 36 . Third, Cy5 was linked to the siR‐slc44a1 for comparing the stability of siR‐slc44a1 in the nano‐windmill system and siR‐slc44a1 alone by observing the degradation of siR‐slc44a1.…”
Section: Resultsmentioning
confidence: 82%
“…First, results of flow cytometry and immunofluorescence images showed that the nano‐windmill was taken up by bone marrow‐derived macrophages (BMDMs) in large quantities in a short time (Figure 2A,B), which revealed its effectively delivered capacities. Second, the RNase H‐responsive sequence was designed to be degraded after entering the cell (Figure 2C), while siR‐slc44a1 gradually dissociated from the nano‐windmill accompanied by the increase of RNase H concentration, identifying the successful separation of the nano‐windmill into tFNA and siR‐slc44a1 (Figure 2D), which is different from the previous tFNA‐based delivery system that tFNA released siRNA with breaking itself and loosing its intact structure after entry into cells, 33,34 such as the nanobox‐siR system 35 or modification of the S2 chain in tFNA 36 . Third, Cy5 was linked to the siR‐slc44a1 for comparing the stability of siR‐slc44a1 in the nano‐windmill system and siR‐slc44a1 alone by observing the degradation of siR‐slc44a1.…”
Section: Resultsmentioning
confidence: 82%
“…Notably, while this paper focuses on the regulatory role of miRNAs in the RCD pathway, siRNAs, which share a similar structure and function, can also exert silencing effects through the RISC mechanism. 29,32,33 Moreover, siRNAs can be designed to match the base sequences completely, providing stronger specificity and more effective silencing compared to the partial base pairing of miRNAs' seed region ( positions 2-7), and all of the key molecules involved in the RCD pathway can be designed for siRNA-targeting sites. 147 In this review, the role of miRNAs as molecular targeted agents in four modes of regulated cell death in osteoblasts is summarized.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…A TDN-based vertex-multi-sticky end system, 24,31 4. A TDN-based edge-sticky end system, 32 5. A TDN-based RNA-embedded system, 33 6.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Additionally, angiogenic peptidecarrying TDNs also benefit BRONJ prevention. [19] Considering previous reports on siRNA-carrying TDNs, [20,21] we further explored the potential of TLR4-siRNA-carrying TDNs (TDN-TLR4-4siR) to decrease the incidence of BRONJ through reversal of macrophageM1/M2 polarization imbalance.…”
Section: Introductionmentioning
confidence: 99%